Compare the Effectiveness of PLISSIT and Sexual Health Models on Women's Sexual Problems in Tehran, Iran: A Randomized Controlled Trial. (1st November 2014) - Farnam, Farnaz; Janghorbani, Mohsen; Raisi, Firoozeh; Merghati‐Khoei, Effat
Abstract: Introduction: Sexuality is an important aspect of human life and sexual problems are common, but there is limited evidence for cost‐effective treatments of women's sexual dysfunctions. Aims: The aim of this study was to assess whether group therapy such as Sexual Health Model (SHM) can be as effective as individual therapy like Permission, Limited Information, Specific Suggestions, and Intensive Therapy (PLISSIT) model in women with sexual problems. Methods: A randomized controlled trial was conducted between May 2012 and September 2013 in five Tehran, Iran health clinics. Eighty‐four consecutive married women aged 20–52 years, with sexual problems who were admitted for the first time, were recruited and randomized into two groups. The intervention included two therapeutic models: the SHM, which consisted of two sessions of 3 hours of group education, and the PLISSIT model, which required a total of 6 hours of one‐on‐one consultation at an interval of 1–2 weeks. Main Outcome Measures: Sexual function and sexual distress were assessed, respectively, with the Brief Index of Sexual Function for Women and Female Sexual Distress Scale Revised questionnaires. Results: Seven months after intervention, the mean (SD) of the sexual distress score decreased and sexual composite score increased significantly in both groups ( P < 0.001). The overall analysis of repeated measure manova revealed borderline significance differences for combined outcomes between two groups ( P = 0.051). Conclusions: Due to the considerable human resource, time, and cost spent conducting the PLISSIT, it seems that group education based on SHM could be more cost‐efficient and nearly as effective. This conclusion may be more applicable in communities where the treatment of sexual problems is in the beginning stages and where people have not received any sexual education or knowledge during their lifetime.